2021
DOI: 10.1002/ece3.8151
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic significance of the characteristics of simple sequence repeats at the genus level based on the complete chloroplast genome sequences of Cyatheaceae

Abstract: Simple sequence repeats (SSRs), also known as microsatellites, are short tandem repeat sequences with a motif length of 1-6 bp characterized by high variability and codominant inheritance and have been widely used in species identification, genetic diversity studies, and phylogenetic relationship determination (Chmielewski et al., 2015;Dashnow et al., 2015). SSRs are caused by slipped strand mispairing and subsequent errors during DNA replication, repair, and recombination (Levinson & Gutman, 1987). SSRs are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
3
11
0
Order By: Relevance
“…Previously, we noted that distribution characteristics of cp SSRs may provide useful phylogenic information at the genus level [ 48 ]. Here, we further evaluated the phylogenetic significance of mt SSRs based on the mt tree ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we noted that distribution characteristics of cp SSRs may provide useful phylogenic information at the genus level [ 48 ]. Here, we further evaluated the phylogenetic significance of mt SSRs based on the mt tree ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we also identified a total of 20 mtSSRs in O. vulgatum with sizes ranging from 10 to 48 bp. Previously, the distribution characteristics of cp SSRs were found to be capable of providing phylogenetic signals at the genus level [ 48 ]. In this study, similar characteristics were indeed observed in the mtSSRs of O. vulgatum and O. californium .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations in G. mangostana cultivars have been shown by randomly amplified DNA fingerprinting (RAF) and inter simple sequence repeat (ISSR) molecular markers 5557 . Plastomes also contain SSR and long repeats 58,59 . SSR, which is a stretch of 1-6 bp small repeats, is found extensively in different regions of plastome such as the intergenic regions, intron regions, and protein-coding regions 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Plastomes also contain SSR and long repeats 58,59 . SSR, which is a stretch of 1-6 bp small repeats, is found extensively in different regions of plastome such as the intergenic regions, intron regions, and protein-coding regions 23 .…”
Section: Genetic Variations In G Mangostana Cultivars Have Been Shown...mentioning
confidence: 99%
“…In previous study, however, the distribution of SSRs was reported to be lineage-speci c. Ping, Feng, Hao et al (2021) found the distributions of SSRs in Cupressus and Hesperocyparis were highly uniform, and suggested that Callitropsis funebris was closer to Cupressus than other Callitropsis species. Recently, Zhu et al (2021) found that the number, type, and localization of SSRs in the plastomes of Cyatheaceae were inter-genus speci c, which provide valid evidence for the phylogenetic analysis of Cyatheaceae.…”
Section: Diversity Of Ssrs Distribution Patternsmentioning
confidence: 95%